PENGARUH PENGGUNAAN METODE OUTDOR TERHADAP KETERAMPILAN MENULIS PUISI SISWA KELAS V SD INPRES SICINI KABUPATEN GOWA - Andi Sitti Nursaenab; Tasrif Akib; Anzar (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effect of using the outdoor method on the poetry writing skills of fifth-grade students at SD Inpres Sicini, Gowa Regency. This study used a quantitative approach with a pre-experimental method through a One Group Pretest–Posttest design. The subjects were 15 fifth-grade students. Data collection used a poetry writing skills test administered before and after the implementation of the outdoor method in the learning process. The results showed that students' poetry writing skills improved after using the method. The average score for students in the pretest was 55.33, increasing to 84.33 in the posttest. These results indicate that using the outdoor method significantly improved students' poetry writing skills. The outdoor method helps students find inspiration and express their imaginations in verses more easily through direct observation of their surroundings. Therefore, the outdoor method can be used as an effective alternative learning method to improve elementary school students' poetry writing skills.